Historia infantilizada en películas biográficas de animación : Bolívar, el Héroe y Eva de la Argentina - Tzvi Tal (Amnis)
The animated biographies of Simón Bolívar and Eva Perón for children adapt the past to the limitations of the present discourses, both ideologically and politically, and forget what is considered appropriate to the age of the intended audience. Bolívar, the Hero reiterates the image of the predestined hero, while Eva de la Argentina demonstrates that the hero is product of his social experience. The Colombian film fails to impact the spectators because the imitation of the Japanese anime aesthetics, it is demobilizing and unattractive, represents women as stereotypical sexual objects. The Argentine film portrays a biography that values the process of innocence to militancy, avoiding aspects that can be homologated to the liberal-oligarchic discourse and representing the protagonist with respect, as historical subject.